National Records and the Impact of International Conflicts on them: the Iraqi Case - Ahmed, Mustafa Hamdi; Dwairi, Khaldoon M. AL (Journal of Cultural Analysis and Social Change, 2025)
International conflicts, wars and crises have multiple impacts on countries, including economic, political, military and cultural ones. The 2003 invasion of Iraq by a U.S.-led coalition not only reshaped the political and security landscape of the Middle East but also initiated a controversial chapter in the management and ownership of Iraq’s cultural and historical records. In the aftermath of the invasion, a vast trove of official Iraqi documents ranging from Ba'ath Party archives to intelligence files was seized and subsequently transferred to various institutions in the United States for analysis, preservation, and, in some cases, public access. Millions of Iraqi documents were subjected to translation, organization, and scanning in order to benefit from the information contained in those documents. This study attempted to trace the fate of Iraqi documents within American institutions.